Underwater noise from geotechnical drilling and standard penetration testing - Erbe, Christine; McPherson, C. (Acoustical Society of America, 2017)
© 2017 Acoustical Society of America. Geotechnical site investigations prior to marine construction typically involve shallow, small-core drilling and standard penetration testing (SPT), during which a small tube is hammered into the ground at the bottom of the borehole. Drilling (120 kW, 83 mm diameter drillbit, 1500 rpm, 16–17 m drill depth in sand and mudstone) and SPT (50 mm diameter test tube, 15 mm wall thickness, 100 kg hammer, 1 m drop height) by a jack-up rig in 7–13 m of water were recorded with a drifting hydrophone at 10–50 m range. Source levels were 142–145 dB re 1 μPa rms @ 1 m (30–2000 Hz) for drilling and 151–160 dB re 1 μPa2s @ 1 m (20–24 000 Hz) for SPT.